Core-shell or Janus-like Fe0.5Ni0.5 nanostructures: A theoretical and experimental study - J. Rojas-Nunez; R.M. Freire; A.L. Elias; K. Fujisawa; L. Troncoso; J.C. Denardin; N. Plaza-Alcafuz; S.E. Baltazar (Journal of Materials Research and Technology)
In this work, the formation FeNi bimetallic nanoparticles was investigated from an experimental and theoretical point of view. Molecular dynamics simulations were carried out in order to know the most stable arrangement of Fe and Ni atoms. The simulations considered nanostructures with three different sizes (6231, 10,000, and 21,366 atoms), and the configurations were forced to have Fe/Ni ratios approximately equal to one. The theoretical results pointed out the formation of an FeNi3 crystalline phase. Also, for different nanoparticle sizes, the lowest energy and stable structure is the Core-Shell FeNi3@Fe, even though the energy difference with the Janus-like structure (JN FeNi3/Fe) structure gets narrower as the number of atoms of the nanostructure increases. Considering these results, the synthesis of the FeNi bimetallic nanoparticles was carried out, and core-shell and Janus-like morphologies were expected to be seen. Interestingly, only core-shell NPs were observed through TEM and HAADF-STEM results, which clearly evidences the interference of the oleylamine (OAm) on the atomic arrangement of the final nanostructure. Based on the experimental results, as well as their discrepancy when compared to the theoretical ones, our hypothesis is that oleylamine is able to guide the nanostructure formation towards a core-shell morphology, by avoiding the appearance of Fe-rich agglomerates and by providing an active interactional site for OAm-Fe complexes with subsequent reduction on the surface of the FeNi3 core. As a result, Fe0 shell is produced, giving rise to a core-shell nanostructure.